Gluten‐free diet impact on dynamics of pancreatic islet‐specific autoimmunity detected at celiac disease diagnosis. Issue 5 (8th June 2020) - Tiberti, Claudio; Montuori, Monica; Trovato, Chiara Maria; Panimolle, Francesca; Filardi, Tiziana; Valitutti, Francesco; Lenzi, Andrea; Cucchiara, Salvatore; Morano, Susanna
Abstract: Objective: Almost 6% of celiac disease (CD) patients at diagnosis are positive for at least one of the main pancreatic islet autoantibodies that characterize type 1 diabetes (T1D). Few information, dated back to almost two decades ago, exist as to whether a gluten‐free diet (GFD) could reduce the islet‐specific autoimmunity detected in patients at CD diagnosis. Aim of the study was to evaluate the impact of GFD on 31 patients who presented islet‐specific autoimmunity at CD diagnosis. Methods: CD patient sera collected at diagnosis and throughout the GFD were analyzed for the main humoral autoantibodies so far identified in T1D, directed against one or more among insulin, glutamic‐acid decarboxylase, tyrosine‐phosphatase 2, and zinc cation‐efflux transporter autoantigens. Results: GFD (median duration 39 months) was associated to a decrease or disappearance of the islet‐specific autoantibodies in 71% of CD patients. Almost 80% of the patients who became autoantibody‐negative during the GFD were positive for only one of the islet‐specific autoimmune markers at CD diagnosis, with none of them developing diabetes. Conversely, 80% of the CD patients positive at diagnosis for ≥2 islet‐specific autoantibodies were still positive after more than two years of GFD, with 25% of them developing T1D. Conclusions: Various factors appear to influence, individually or in combination, the effects of the GFD on pancreatic islet‐specific autoimmune response detected at CD diagnosis. These factors include the number of diabetes autoantibodies found at CD diagnosis, the adherence to the GFD, its duration and an asymptomatic clinical presentation of CD.